Grenzziehungen und Grenzbeziehungen des Disziplinären Verhältnisbestimmungen (in) der Erziehungswissenschaft - Hofbauer, Susann; Schreiber, Felix; Vogel, Katharina (Beiträge zur Theorie und Geschichte der Erziehungswissenschaft, 2023)
The attempts to talk about educational science, to measure it and to give it a certain theoretical and systematic order go hand in hand with the definition of its boundaries and relationships. This volume looks at discursive inclusions and exclusions, the 'in-between' positioning of educational science, the drawing, shifting and debating of boundaries to the 'social outside' by the 'educational science inside'. The logics of reception and participation in educational science discourses, the establishment of sub-disciplines, the organisation of science policy controls or the utilisation of findings are just as relevant as methodologically reconstructive relationships.